Edge Node Detection For Better Data Transmission Under The Queuing Network Using Pipelining In Mobile AD HOC Network - Vijaya, G.K; Bharathidass, S (International Journal of Computer Sciences and Engineering, 2025)
Mobile Ad-hoc Networks (MANETs) is an autonomous system of mobile nodes connected by wireless links; the mobile nodes are available to run in any direction. MANETs are usually formed without any significant infrastructure also its depended on opened queuing network. As a result, they are almost exposed to the traffic observer that target damage, who try to block the data packets by compromising nodes and trace the data transmission direction. Therefore, detecting the edge node is an essential part in MANETs. It is easy to observe a node that induces edge node activity in other nodes, but very difficult to identify a node which is passively observing and misusing network data. In this work, we propose stack optimization based on Edge Node Detecting through Piping Queue (ENDPQ) for Secure Data Transmission in MANETs. Also, a novel approach using node duplication method and two hop neighbor discovery method using which the location of the node can be verified. The source node performs two-hop neighbor discovery to collect the neighbor nodes and perform node duplication method to ascertain the location of the node being selected to route the packet. The proposed plan reduces the overhead introduced by verification procedure and increases the network performance